Cognitive and emotional processing in brothers of individuals with anorexia nervosa: exploring familial cognitive vulnerability - Meneguzzo, Paolo; Ceccato, Enrico; Sala, Alessandra; Santonastaso, Paolo (Frontiers in Psychiatry, 2025)
BackgroundAnorexia nervosa (AN) is associated with altered cognitive and emotional traits, including deficits in empathy, theory of mind (ToM), and increased alexithymia. While these traits are well-documented in affected individuals, little is known about their presence in unaffected male siblings, who share genetic and environmental risk factors. This study investigates whether male siblings of women with AN (bAN) exhibit intermediate cognitive-emotional traits compared to both their affected sisters and general population (GP) controls.MethodsWe assessed 31 bAN, 31 GP, and 31 affected sisters. Participants completed self-report questionnaires (Empathy Quotient, Toronto Alexithymia Scale, Eating Disorder Examination Questionnaire) and two computerized tasks evaluating theory of mind (Story-based Empathy Task (SET), Reading the Mind in the Eyes Task). Between-group differences were assessed using non-parametric tests due to the non-normality of the data. A binary logistic regression was then conducted to evaluate whether specific socio-cognitive variables predicted group membership.ResultsbAN showed significantly lower scores than the GP on measures of cognitive empathy and theory of mind, particularly Causal Inference (SET-CI; r = 0.594, p < 0.001), Emotional Attribution (SET-EA; r = 0.520, p < 0.001), and Intention Attribution (SET-IA; r = 0.463, p = 0.001). Logistic regression identified SET-CI as the strongest predictor of bAN status. Other empathy and alexithymia measures showed no significant group differences.ConclusionThese findings suggest that domain-general inferential difficulties—particularly in causal reasoning—may be associated with familial vulnerability to anorexia nervosa in male siblings. Further research is needed to clarify the role of such cognitive traits in the broader context of risk and to inform early identification and intervention strategies.